Fossil hymenosomatid crabs (Crustacea: Decapoda) from the Lower Cretaceous of NE Brazil - Mendes, Ighor Dienes; Santana, William [UNESP]; Carvalho, Ismar de Souza (Elsevier, 2022)
Hymenosomatidae is an eubrachyuran family of small and fragile crabs known until now only by extant species of two subfamilies. Here we describe and illustrate a new subfamily (Eureotropisinae subfam. nov.), two new genera (Eureotropis gen. nov., Protohymenosoma gen. nov.) and three new species (Eureotropis elongata gen. et sp. nov., Protohymenosoma gondwanicum gen. et sp. nov., P. hexagonale gen. et sp. nov.) of Hymenosomatidae from the upper Barremian (Lower Cretaceous) of Sergipe-Alagoas Basin, northeastern Brazil. The fossil material studied here is the first record of Hymenosomatidae and one of the oldest eubrachyuran fossils described along with the majoid Cretamaja klompmakeri. The fossil crabs were found in bivalve-rich carbonates, accumulated in a rift lake system, from the early stages of the South Atlantic opening, during episodic marine incursions. The new subfamily and species described provide evidence of a long-time Mesozoic lineage of the Hymenosomatidae, distinct from the Oligocene origin hypothesis currently adopted. This also supports a Gondwanan origin hypothesis and a later worldwide pattern of distribution of the extant taxa. In addition, our data indicate the colonization of the proto-South Atlantic by coastal marine eubrachyurans during the late Barremian.
Keywords: Cretaceous; Decapoda; Hymenosomatidae; Hymenosomatoidea; late Barremian; proto-South Atlantic